Seismological tools for geothermal exploration and monitoring ... : Seismologische Tools zur geothermischen Exploration und Überwachung ... - Toledo Zambrano, Tania Andrea (Technische Universität Berlin, 2021)
Important aspects of geothermal exploration and exploitation are the assessment and mitigation of natural and/or induced seismicity, the imaging and resource assessment of a geothermal reservoir and the monitoring of the effects of the exploitation activities. With this thesis the analysis and application of various seismological tools for the planning, exploration, and monitoring of geothermal fields are given. The methods explored and further developed include survey design for microseismic network construction and assessment, local earthquake tomography, ambient noise tomography, and coda wave interferometry. These techniques were applied to study Los Humeros (Mexico), Theistareykir (Iceland) and Reykjanes (Iceland) geothermal fields. The geometry of seismological arrays is essential for high quality seismic event retrieval and minimal location errors. A sequential survey design algorithm that uses a quality measure based on the D-criterion was applied to extend the seismic network at Theistareykir and to ... : Wichtige Aspekte der geothermischen Exploration und Nutzung sind die Bewertung und Reduzierung der natürlichen und/oder induzierten Seismizität, die Abbildung und Ressourcenbewertung eines geothermischen Reservoirs, sowie die Überwachung der Auswirkungen der Explorationsaktivitäten. In dieser Arbeit werden die Analysen und Anwendungen verschiedener seismologischer Methoden zur Planung, Erkundung und Überwachung geothermischer Felder vorgestellt. Die untersuchten und hier weiterentwickelten Methoden umfassen das Design für den Aufbau und die Bewertung mikroseismischer Netzwerke, die lokale Erdbebentomographie, die Ambient-Noise-Tomographie und die Coda-Wellen-Interferometrie. Diese Techniken werden angewendet, um die geothermischen Felder Los Humeros (Mexiko), Theistareykir (Island) und Reykjanes (Island) zu untersuchen. Die Geometrie seismologischer Arrays ist essentiell für eine gute Bestimmung seismischer Ereignisse mit kleinen Lokationsungenauigkeiten. Ein sequenzieller Algorithmus zum Design des Arrays, ...